2011
DOI: 10.1103/physrevlett.107.036801
|View full text |Cite
|
Sign up to set email alerts
|

Majorana Edge States in Interacting One-Dimensional Systems

Abstract: We show that one-dimensional electron systems in the proximity of a superconductor that support Majorana edge states are extremely susceptible to electron-electron interactions. Strong interactions generically destroy the induced superconducting gap that stabilizes the Majorana edge states. For weak interactions, the renormalization of the gap is nonuniversal and allows for a regime in which the Majorana edge states persist. We present strategies of how this regime can be reached.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
301
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(315 citation statements)
references
References 33 publications
11
301
1
2
Order By: Relevance
“…The interactions involved in Majorana zero-energy pinning are not intrinsic to the wire, 18,[21][22][23][24][25][26][27][28] but rather extrinsic, between electrons that enter the wire and bound charges in the dielectric environment that arise in response. Our results suggest that such electronic interactions provide a powerful mechanism to stabilize Majorana-based qubits in realistic nanowires, and may account for the hitherto unexplained experimental features.…”
Section: Introductionmentioning
confidence: 99%
“…The interactions involved in Majorana zero-energy pinning are not intrinsic to the wire, 18,[21][22][23][24][25][26][27][28] but rather extrinsic, between electrons that enter the wire and bound charges in the dielectric environment that arise in response. Our results suggest that such electronic interactions provide a powerful mechanism to stabilize Majorana-based qubits in realistic nanowires, and may account for the hitherto unexplained experimental features.…”
Section: Introductionmentioning
confidence: 99%
“…For example, considerable progress has been made towards developing number preserving theories of the Majorana modes, [15][16][17][18][19][20] as well as a growing body of work which examines how free-topological superconducting phases are affected by the addition of interacting electron-electron terms. [21][22][23][24][25][26][27][28][29][30][31][32][33] One aspect of this latter story is concerned with the stability and structure of the Majorana zero-modes themselves and how they are affected by the presence of density-density interaction terms that break the exactly solvable nature of the underlying model. The issue of stable zero-modes has also been addressed in the related context of 1-d parafermionic chains.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. 23 it was shown that, when the p-wave system can be bosonized, a refermionization argument indicates the continued stability of the modes in interacting regions of the topological phase. Importantly, this argument does not require the restriction to an odd number of Majorana modes.…”
Section: Introductionmentioning
confidence: 99%
“…Majorana fermions 1 (MFs), being their own antiparticles, have attracted much attention in recent years in condensed matter physics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Besides being of fundamental interest, these exotic quantum particles have the potential for being used in topological quantum computing due to their non-Abelian statistics [20][21][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%